Day of Week Effect on Financial Market: Evidence in Vietnam during Normal Period and COVID-19 Pandemic - Tran, Thuy Nhung (KINERJA, 2023)
The article is focused on examining the existence of the day-of-the-week (DOW) effect on the Vietnamese stock market. This study uses the daily series of closed market indexes data from 2014 to 2021 and extends to a deep-dive review of the outbreak period of the COVID-19 pandemic. Furthermore, the regression model with dummy variables and parametric and non-parametric methods are employed to identify the existence of the DOW effect on stock market returns and volatility. The empirical results obtained from the above models have demonstrated that the day-of-the-week effect impacts stock returns shown in three out of four indices, especially on Mondays and Fridays. At the same time, no statistical evidence supports the presence of any significant daily patterns for either the COVID-19 outbreak phase or in the HNX30. Particularly, the highest return occurs on Monday, and the lowest volatility usually appears on Friday in all three HOSE Indexes. This study contributed further evidence for not only the presence of the day-of-the-effect patterns on the Vietnamese stock market but also path the ways to analyze the stock returns and variance of financial assets during the COVID-19 epidemic.